A space-efficient fast prime number sieve - Dunten, Brian; Jones, Julie; Sorenson, Jonathan (Information processing letters, 1996)
We present a new algorithm that finds all primes up to n using at most O( n log log n ) arithmetic operations and O( n (log n log log n) ) space. This algorithm is an improvement of a linear prime number sieve due to Pritchard. Our new algorithm matches the running time of the best previous prime number sieve, but uses less space by a factor of Θ ( log n). In addition, we present the results of our implementations of most known prime number sieves.